Evidências sobre práticas Environmental, Social e Governance (ESG) associadas ao custo de capital das empresas no mercado de capitais nos países do G2 - Carvalho, Patrícia Lacerda de (2023)
This thesis is dedicated to the analysis of the relationship between Environmental, Social and Governance (ESG) practices and the costs of equity and costs of debt of companies in the capital market in the G20 countries. The literature points out that the financial model of ESG socially responsible investing is now the standard approach across the world and it is reflected in ESG metrics, ratings, guidance and regulatory rules. In this line of reasoning, this study is based on the premise that ESG practices are a legitimizing factor for the reduction in companies’ capital costs. In the data analysis, 19 countries of the G20 were considered, excluding, in this case, only the European Union. The selection of countries chosen for the investigation considered economies that are committed to supporting sustainability and that are distributed between developed countries (G8) and emerging countries (G11). The Panel Data methodology was used, in a sample of 3,651 companies in 17 years, corresponding to the period from 2005 to 2021. To carry out this study, understanding that ESG practices have different approaches and metrics, the ESG score meter from Refinitiv and Bloomberg platforms was used, considering ESG performance and ESG disclosure, respectively. Refinitiv’s ESG performance focuses on measuring and tracking companies’ performance as well as the environmental, social and governance impact of these companies. From another perspective, Bloomberg’s ESG disclosure level focuses on providing companies with a metric on disclosing ESG data and information, enabling investors and stakeholders to better understand and evaluate a company’s ESG practices. In the correlation analysis, it was found that there is no perfect correlation between the ESG performance and the ESG disclosure scores, as expected by the capital market, that is, leading to the inference that the indices capture different attributes. As for the results, they show that there is a negative and significant relationship between companies’ ESG practices and their cost of capital in the 19 countries of the G20. When analyzing ESG practices broken down into their dimensions, the social factor had the greatest negative effect on costs, both in relation to ESG performance and in ESG disclosure. ESG disclosure can only be considered a moderating factor between ESG performance and third-party capital costs, however in a weak relationship. Furthermore, the impact of ESG practices on reducing capital costs is greater in companies from developed countries (G8) than in emerging countries (G11). However, when analyzing the cost of debt, the effect of ESG practices reduces costs in the G11, which does not occur with the cost of equity. A possible reflection is that the scores of ESG practices in emerging countries may be in a progressive stage, not yet impacting the reduction of equity. In general, it is evident that successful ESG practices can generate tangible benefits in reducing the cost of capital for companies and it deserves a careful look from investors in the context of investment management.